Analisis Payback Period Sebagai Dasar Kelayakan Investasi - Wati, Murna (Jurnal Daya Saing, 2016)
Abstract: Investment is the main decision finances for the long term usually requires a large amount of funds that need to be analyzed in depth before running out investment activities, investment can basically refers to the economic activity of a country , the activity of investment is economically is advantageous , Interest Eligibility investing is to find out how large rate advantages gained by using a pay back period, as the basis for this effort is feasible to be implemented. This research uses descriptive method with survey approach is to use secondary data is data that has been processed and the data provided in the company terssebut. The data analysis of this research by using quantitative descriptive method describes the reality of the matter with their efforts to resolve problems in a certain period. The data to the analysis of this research by using quantitative descriptive method describes the reality of the matter with Reviews their Efforts to resolve problems in a Certain Period Keywords: Feasibility, Investment